MANGO (Mangifera indica) KERNEL STARCH PUDDING : RHEOLOGICAL, TEXTURAL AND SENSORY PROPERTIES - SHAHZAD HUSSAIN; Abdellatif A. Mohamed; Abdulrahman Alahmed; Mohamed. A. Ibraheem; Akram. A. Qasem; Basim M. Alohali (Journal of Animal and Plant Sciences, 2026)
Agro-industrial by-products are widely utilized to make a variety of products, including food ingredients. The fruit of the mango is composed of 35–60% by-products such as peel and seeds, while the kernel accounts for 45–75% of the seed mass. Because mango kernel has a high starch content, it can be utilized directly for pudding formulations without further processing. Mango kernel starch (MKS) was isolated for comparison with corn starch (CS), the starch most commonly used as an ingredient in puddings. The experiment was conducted using a Completely Randomized Design (CRD), with four treatments (0, 50, 75, and 100% MKS substitution), each replicated 3 times depending on the analysis type.Rapid visco analyser, rheometer, texture analyser, and sensory evaluation were used to test the pudding samples. MKS pudding (all substitution levels) had significantly greater peak viscosity (PV) than pudding made with corn starch (CS). Compared to the pudding containing CS, the MKS pudding had a significantly (p < 0.05) higher final viscosity and setback. All MKS-pudding showed reduced cohesion and increased gel hardness. As a result, the final gels with higher MKS content required less penetration energy. In terms of cohesion, panellists’ overall acceptance, and pudding hardness, samples containing 50 or 75% MKS were preferred in terms of cohesion, hardness, and overall acceptability. Comparing MKS-pudding to a commercial sample, the former performed better. Based on the data collected in this research, ground mango kernel shows promise as a cost-effective and sustainable starch source for pudding formulations.
Keywords: mango kernel starch; pasting; texture; pudding; sensory